REVISION OF LEGAL AND ADMINISTRATIVE REGULATION IMPACT ON THE DIVERSITY OF FUNDING OF SPORTS CLUBS: IRAQ EXPERIENCE - Сауд Саад Джасім (Фінансово-кредитна діяльність: проблеми теорії та практики)
The research proposes to recognize the impact of legal and administrative regulation revision on the diversity of funding sources and its reflection on improving the activities of Iraqi clubs and their continuity from the point of view of some academics and club officials. To reach the goal, a field study was conducted at the level of sports clubs in Thi Qar Governorate / Iraq, where the descriptive approach was used in the theoretical aspect and the case study in the applied aspect, and the questionnaire with the five-point Likert scale was adopted as a tool for collecting data, by sending the questionnaire electronically to the research community consisting of 37 people between academics and club officials, where the answers were retrieved from a sample consisting of thirty-four (34) of them, and the questionnaire was examined by the Statistical Package for Social Sciences (SPSS) program. The results revealed that sports clubs in Thi Qar Governorate suffer from many problems in the financial aspect due to the lack of available financial funding sources, as they depend on traditional sources of funding such as state subsidies, as government funding for clubs is available, but it is not sufficient. Moreover, the results also revealed that there is a positive impact of the diversity of funding sources on improving the activities of sports clubs and their continuity.